Green Banking Initiatives: Policy and Practices in Commercial Banks of Nepal - Tiwari, Ghanashyam (INTELLIGENCE Journal of Multidisciplinary Research, 2024)
Environmental and social (E&S) risk management has grown in key aspects of sustainability in banks and other financial institutions these days. A socially inclusive, climate-friendly and green banking system is only possible with the effective management of E&S risk in their business transactions. This study assesses the present implementation status of sustainability within commercial banks in Nepal, by examining their adherence to the environment and social risk (ESRM) guidelines issued by Nepal Rastra Bank (NRB). Using a descriptive research design, the study utilizes ESRM reports published by NRB in 2078/79 and 2079/80. The study examines the present state of ESRM guideline implementation across three key aspects of policy formation, training and development activities for bank employees, and incorporation of environmental and social risks within the core strategies of commercial banks. The result found a satisfactory level of implementation of ESRM guidelines. The policy formulation and governance indicators are almost realized and other indicators have satisfactory and progressive levels of operation in the banks. Effective implementation of sustainable guidelines and initiatives will be accomplished innovative financial instruments that incentivize green investments and support climate-resilient practices can further expedite the transition to a sustainable banking landscape. Overall, this study offers valuable insights into the current state of ESRM in Nepal's commercial banks, shedding light on the progress that can pave the way for a more sustainable and green financial system in Nepal.